Clustering and modeling joint-trajectories of HIV/AIDS and tuberculosis mortality rates using bayesian multi-process latent growth model: A global study from 1990 to 2021 - Tofigh Mobaderi; Anoshirvan Kazemnejad; Masoud Salehi (BMC Infectious Diseases)
Abstract Background The bidirectional association of HIV/AIDS and Tuberculosis (TB) presents significant global health challenges. However, the relationship between these dual epidemics and the heterogeneity in their mortality rate patterns have not been properly addressed. Therefore, the aim of this study was to cluster and model the joint trajectories of HIV/AIDS and TB mortality rates from 1990 to 2021 worldwide. Methods In this longitudinal study, the HIV/AIDS and TB mortality rates data for 204 countries from 1990 to 2021 were obtained from the global burden of disease database. The longitudinal k-means clustering approach was utilized to categorize countries into homogeneous subgroups based on the joint patterns of HIV/AIDS and TB mortality rates. Subsequently, the Bayesian multi-process nonlinear Latent Growth Model (LGM) was conducted to concurrently estimate the patterns of HIV/AIDS and TB mortality rates. Results The average global TB mortality rates dropped from 30.61 to 13.34 per 100,000 between 1990 and 2021. Meanwhile, the average HIV/AIDS mortality rates rose from 10.94 to 48.42 per 100,000 by 2000 before declining to 16.90 per 100,000 in 2021. The Bayesian multi-process nonlinear LGM indicated that the intercepts for the overall HIV/AIDS and TB models were 11.168 and 30.184, and the slopes were 16.104 and − 1.040, respectively. This suggests that the initial HIV/AIDS and TB mortality rates were 11.168 and 30.184 persons per 100,000, and the rates of change were 16.104 and − 1.040 persons per 100,000 every five years. However, the strength and direction of the rate of change were dependent on the factor loading scores, as they exhibited a nonlinear trend. Finally, the 204 countries were clustered into three distinct subgroups, each with different intercepts and slopes. Cluster A demonstrated the lowest HIV/AIDS and TB mortality rates throughout the study, while Cluster C exhibited the highest mortality rates. Conclusions Although the overall global HIV/AIDS and TB mortality rates have declined, Southern African countries continue to bear a significant burden of HIV/AIDS and TB, with no significant reduction observed in TB mortality rates from 1990 to 2021. Therefore, prioritizing these countries is crucial to achieving the Sustainable Development Goals (SDGs) of eradicating the global HIV/AIDS and TB epidemics by 2030 and 2035, respectively.